HUBUNGAN ANTARA TINGKAT EMOTIONAL QUOTIENT (EQ) DENGAN PRESTASI ATLET PENCAK SILAT KATEGORI TANDING PUTRI (Universitas Negeri Semarang, 2016)
Background issues: Is there a relationship between the level of Emotional Quotient (EQ) with Pencak Silat Athletes Achievement Category Slam POM Rayon 1 Daughter in Central Java province in 2015 The method used in this research is the survey method tests. The population in this study were all women athletes amounted to 34 athletes. Total sampling using Sampiling. The variable in this study is the level of Emotional Quotient (EQ) as well as the independent variables athlete achievement martial arts sparring category as the dependent variable. The conclusions of this research are: There is a relationship between the level of Emotional Quotient (EQ) with the athlete's performance of martial arts sparring category POM Rayon 1 daughter in Central Java province in 2015. Suggestions for trainers in order to train the emotions of their students. So that their students can be controlled emotion during games and also for the athletes of martial arts in order to control the emotions themselves in order to obtain satisfactory progress.